Distinct distribution patterns of planktonic ciliate communities along environmental gradients in a semi-enclosed bay - Yunpeng Liu; Yi Dong; Feng Zhao; Shan Zheng; Chaofeng Wang; Wuchang Zhang (Ecological Indicators, 2022)
Jiaozhou Bay is a representative temperate coastal ecosystem and connects with the Yellow Sea by a narrow mouth. The eastern part of the Bay is more polluted than the western and outer parts due to the combined effects of urban sewage and weak water exchange between different water masses. However, the previous results from microscopy analyses did not show any distinct distribution pattern of planktonic ciliates, which are generally considered good bioindicators along environmental gradients. We hypothesize that ciliates may respond to environmental stress by regulating the community of rare taxa, which was not uncovered by morphological methods. The diversity and distribution patterns of planktonic ciliate communities were investigated through high-throughput DNA sequencing from 13 stations in the eastern, western and outer parts of Jiaozhou Bay. The alpha diversity indices showed an increasing trend from the east Bay to the west Bay to the outer Bay. Significant differences in planktonic ciliate communities from different zones of the Bay were mainly attributed to rare rather than abundant taxa. Correlation network analysis revealed that the rare taxa generally have positive correlations with other rare ones, while more negative correlations were found among abundant taxa. We further revealed the distributions of three dominant genera (Stenosemella, Tintinnopsis, and Strombidium) were significantly correlated with environmental variables, suggesting that they might be used as ecological indicators. Our results elucidate the bioindicator potential of ciliate along environmental gradients in a semi-enclosed bay.